Evaluating Knowledge, Attitude, and Behavior of Dentists on HIV/AIDS in West Java, Indonesia, in the COVID-19 Era - Irna Sufiawati; Muhammad Arib Rafi; Fidya Meditia Putri (International Journal of Dentistry)
Purpose. HIV/AIDS is still a serious public health problem in Indonesia. It has been concerned that the coronavirus disease 2019 (COVID-19) pandemic has a serious impact on people living with HIV (PLWH). Therefore, dentists remain to have a significant role to play in the overall healthcare delivery to PLWH and reducing new HIV infections. The purpose of this study was to assess the knowledge, attitudes, and behavior of dentists in West Java about HIV/AIDS in the COVID-19 era. Methods. This cross-sectional study was conducted by distributing online questionnaires using a Google form to dentists in West Java. We used the purposive sampling technique to recruit the participants. The questionnaire consists of characteristics of respondents, 13 questions about knowledge, 9 questions about attitudes, and 6 questions about behaviors, which has previously been tested for validity and reliability. Data were analyzed using the Spearman correlation test and the Chi-square test. Results. The Questionnaire was sent to 435 dentists in the West Java region, Indonesia, with the assistance of the Indonesian Dental Association West Java region, to participate in this study. We received completed questionnaires from 209 (48%) respondents. The results of this study showed that 44% of dentists have good knowledge, 53% have a positive attitude, and 53% have positive behavior. No significant relationship was found between knowledge and attitudes (p=0.202) and behavior (p=0.087), but there was a significant relationship between attitudes and behavior (p=0.0001). Conclusion. About half of the dentists in West Java have good knowledge, positive attitudes, and behavior towards HIV/AIDS, but the others lack knowledge, negative attitudes, and behavior. Continuing HIV/AIDS education and training programs for dentists are still needed to keep improving their knowledge and awareness to support disease prevention and control in this COVID-19 era.